Who is the man in the air? : Michael Jordan - Soria, Gabriel; Williams, Brittney, 1989- (New York : Penguin Workshop, 2022)
Explore the relentless grit of Michael Jordan, as he powers through a mysterious illness in Game 5 of the 1997 NBA Finals against the Utah Jazz, infamously known as the Flu Game. A story of athleticism, willpower, and triumph, this graphic novel invites readers to immerse themselves into the unyielding drive of one of the greatest basketball players of all time.
School Library Journal, September 2022
Includes bibliographical references (page 63).
4.4
3-6
Keywords: Jordan, Michael, -- 1963- -- Comic books, strips, etc; Jordan, Michael, -- 1963- -- Juvenile literature; Basketball players -- United States -- Comic books, strips, etc; Basketball players -- United States -- Juvenile literature; African Americans -- Biography -- Comic books, strips, etc; African Americans -- Biography -- Juvenile literature; Jordan, Michael, -- 1963- -- Cartoons and comics; Basketball players -- Cartoons and comics; African Americans -- Biography -- Cartoons and comics; Biographical comics; Nonfiction comics; Comics (Graphic works); Biographies